Resilience and Peer Social Support as Predictors of Students’ Psychological Well-Being during the War in Ukraine - Halyna Meshko; Oleksandr Meshko; Sergii Mamychenko; Natalia Dievochkina (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The ongoing war in Ukraine has significantly disrupted students’ educational experiences and increased their vulnerability to psychological distress, highlighting the need to identify protective factors that sustain well-being. Objective: This study examines the influence of resilience and peer social support on students’ psychological well-being in a war-affected context. Method: A quantitative correlational design was employed involving 120 high school students selected through proportionate stratified random sampling. Data were collected using validated self-report scales and analysed using multiple linear regression. Results: Both resilience and peer social support significantly predict psychological well-being, with resilience emerging as the stronger predictor. Descriptive findings indicate high levels of resilience and peer support, while psychological well-being remains moderate, reflecting the persistent impact of wartime stressors. Conclusion: These findings suggest that internal adaptive capacity and interpersonal support function as complementary protective systems that help students cope with prolonged adversity. Contribution: This study contributes to the development of resilience-based and social support frameworks in conflict settings and provides empirical evidence to inform integrated psychosocial interventions in educational environments.